A Comparative Study On Folk Songs and Western Songs in the Contemporary Tamil Cinema - Iyyanar, M; Jebakumar, C (International Journal of Computer Sciences and Engineering, 2018)
The aim of the research work is to compare the folk songs and western songs in the recent Tamil cinema. Also, this research examines memory and lyrical content of songs in recent Tamil films. In this experimental research, an experiment was carried out to find out the stress factors, memory level of words, and content relevance. A comparative study between the folk songs and western songs was conducted among the viewers of the film audience. The members divided into three groups. Those group members were shown different film songs for thirty minutes. The standardized NSAD stress questionnaire used to study the stress level among the members. The folk songs which are being used in this experimental study are, Naatupurapaatu, Kilakku Seemaiyele, and Enthiran. These film songs are categorized into traditional folk songs, (traditional instruments), modernized folk songs, (fusion of classical and modern instruments), and western songs (computerized instruments). These film’s songs show the differences in lyrics, instruments, fusion and modernized music. This experimental research clearly shows the differences in memory of the lyrics and musical beats. This research shows that there is a development exists in the short-term memory among the viewers. The traditional folk songs play a vital role in the communication process and memory. It helps to convey the story during the film and improve the memory in remembering the story and contents of the film. This research shows that the reduced stress level among the film watchers. The presence of folk media enhances the communication process. This research can be extended to other medium of communication.